Analisis Manajemen Stres Dan Emosi Pada Guru Di Sekolah Negara Jepang Dan Indonesia - Effendi, Muhammad Idris; Dahniar, Nenie; Sulistyowati, Dian (Vocational College of Diponegoro University, 2025)
This study investigates stress and emotion management strategies among teachers in Japanese and Indonesian state schools, focusing on how cultural factors and emotional intelligence influence coping mechanisms. Using a qualitative literature review, the research synthesizes findings from studies published over the last decade. The analysis identifies key themes, including the distinct cultural approaches of each country. Japanese teachers predominantly employ structured professional development and mindfulness practices, reflecting cultural values of self-discipline and emotional control. Conversely, Indonesian teachers rely on community-based support and spirituality, rooted in their communal and religious traditions. The findings highlight the central role of emotional intelligence in managing stress, improving resilience, and fostering effective teaching practices in both settings. Challenges such as high workloads, student discipline, and the rapid shift to online teaching during the COVID-19 pandemic underscore the need for robust coping strategies. The study concludes that culturally tailored interventions, such as mindfulness training for Japanese teachers and community-based workshops for Indonesian teachers, are essential for enhancing teacher well-being and effectiveness. Policymakers and educators should prioritize emotional intelligence development and supportive school environments to address these challenges comprehensively